Transforming the "grammar school" to be more inclusive: the experience of three spanish schools - Cecilia Simón Rueda; Marta Sandoval Mena; Gerardo Echeita Sarrionandia; Cristóbal Calero Gil; Beatriz Nuñez Gutiérrez de San Miguel; Pilar de Sotto Esteban; M. Montserrat Pérez García; Ana Belén García de la Torre (Universidad de La Rioja, 2015)
The aim of this article is to share some of the early reflections made by the researchers and teachers from three Spanish educational centers that are participating in the European project Teaching diverse learners in (School) Subjects) coordinated by Kerstin Merz-Atalik and Heike Tiemann (University of Education Ludwigsburg). From our point of view, if we really want to make progress toward an educational system and schools with capacity to respond with equity and fairness to the student diversity, we will have to radically change the existing "grammar school". Our purpose will be to show some of the key elements that have been changed in the three participating centres, to try to ensure the balance between quality and educational equity from the reality of each one. Based on the analysis of the main barriers and challenges to move toward an inclusive education, here are listed some of the elements that have been necessary to transform in these educational institutions in order to shorten the distance between the declared values and specific practices.